Multi-omics revealed that the postbiotic of hawthorn-probiotic alleviated constipation caused by loperamide in elderly mice - Wei, Yu; Chen, Shuai; Ling, Ying; Wang, Wei; Huang, Yali (Frontiers in Nutrition, 2025)
BackgroundConstipation is a prevalent and recurrent gastrointestinal disorder causing significant discomfort. However, current treatments often prove ineffective. Previous research indicates that the postbiotic derived from a combination of hawthorn and probiotics can alleviate constipation. This study aimed to investigate its mechanisms using loperamide-induced constipation in aged KM mice.MethodsConstipated mice were divided into groups receiving 10% lactulose (Y), hawthorn extract (S), probiotics (F), and the postbiotic of hawthorn-probiotic (FS). UPLC–MS metabolomics identified constituents of F, S, and FS. Network pharmacological analysis identified targets affected by FS. RT-qPCR assessed target expression in mouse colons, along with IL-6 and IL-17A levels. Molecular docking with AutoDock Tools1.5.6 evaluated interactions between FS components and targets. ex vivo colonic organ culture and RT-qPCR assessed target changes. Molecular dynamics analysis further scrutinized interactions. Targeted metabolomics measured short-chain fatty acid levels in mouse stool.ResultsUPLC–MS metabolomics revealed distinct profiles for F, S, and FS, with FS showing decreased toxic substances and increased beneficial ones compared to S. Network pharmacology identified 20 cross-targets of FS in constipation. RT-qPCR showed decreased NR1I2 and SULT1A1 and increased GLP-2r in FS-treated mice. Inflammatory cytokines IL-6 and IL-17A were also reduced. ex vivo colonic organ culture and molecular docking identified effective combinations such as TNF-Baicalin and AQP3-Quinacridone. RMSD, RMSF, and RG analyses indicated favorable interactions between small molecules and targets. Targeted metabolomics revealed differing short-chain fatty acid contents in feces among groups.ConclusionThe postbiotic of hawthorn-probiotic alleviates constipation by regulating intestinal water and sodium metabolism, maintaining the intestinal barrier and gut flora, promoting epithelial cell proliferation, reducing inflammatory responses, and improving short-chain fatty acid metabolism.